Cash wage payments in transition economies: Consequences of envelope wages - Ioana Alexandra Horodnic; Colin C. Williams (IZA World of Labor, 2021)
In transition economies, a significant number of companies reduce their tax and social contributions by paying their staff an official salary, described in a registered formal employment agreement, and an extra, undeclared "envelope wage," via a verbal unwritten agreement. The consequences include a loss of government income and a lack of fair play for lawful companies. For employees, accepting under-reported wages reduces their access to credit and their social protections. Addressing this issue will help increase the quality of working conditions, strengthen trade unions, and reduce unfair competition.
Keywords: J46; J48; O17; E26; 330; envelope wages; informal employment; undeclared economy; tax evasion